Design of A Rectangular Patch Microstrip Array Antenna with Proximity Coupled On ADS-B Receiver - Muhammad Fauzi Manalu; Muh. Wildan; M. Faisal Yoga Dewantara; Priyo Wibowo (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
One of the observation facilities available in Indonesia was Automatic Dependent Surveillance-Broadcast (ADS-B), a surveillance technology similar to Radio Detection and Ranging for monitoring air traffic. This system only received information transmissions from aircraft, broadcast on a frequency of 1090 MHz using a monopole antenna with large dimensions, ranging from 85 centimeters to 3,5 meters, and weighing between 1,5 kilograms to 26 kilograms. As an alternative, a microstrip antenna was chosen to reduce the large size and weight of the monopole antenna. This research aimed to design a 2x1 rectangular patch microstrip array antenna with a proximity coupled feeding method at a frequency of 1090 MHz. The antenna was designed using Antenna Design Software and fabricated using Epoxy substrate material with a copper ground plane. The simulation results showed a Return Loss of -28,87 decibels, VSWR 1,07, Bandwidth 28,87 MHz, Impedance 52,4 Ω, and Gain 8,49 decibels. The measurement results showed a Return Loss of -30,87 decibels, VSWR 1,07, Bandwidth 28 MHz, Impedance 48,91 Ω, and Gain 6,4 decibels. The test results demonstrated that the antenna successfully received signals from 32 aircraft, with the longest reception distance reaching 172,5 Nautical Miles (319.4 kilometer) at a maximum altitude of 36,950 feet.